2020
DOI: 10.3390/su12124972
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility and Maturity Mismatch of Investment and Financing: Evidence from Polluting and Non-Polluting Companies

Abstract: We investigate the influence of corporate social responsibility (CSR) on the maturity mismatch of investment and financing from the perspective of both polluting and non-polluting companies. The results reveal that CSR performance can aggravate the maturity mismatch of investment and financing; and the effect can be more serious in the polluting companies. At the same time, we find that CSR makes companies obtain more short-term debt. What is more, polluting companies perform more environmental responsibilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Thirdly, the third sectors, companies and the public should be encouraged in air protection. Some empirical analyses have been shown that Environmental Non-Governmental Organizations (ENGOs) and companies have a positive impact on the improvement of environmental quality (Bao et al, 2020;Li et al, 2021). Local people can be mobilized and organized by ENGOs and companies to participate in environmental improvement activities , which will alleviate the pressure of governments on environmental protection.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the third sectors, companies and the public should be encouraged in air protection. Some empirical analyses have been shown that Environmental Non-Governmental Organizations (ENGOs) and companies have a positive impact on the improvement of environmental quality (Bao et al, 2020;Li et al, 2021). Local people can be mobilized and organized by ENGOs and companies to participate in environmental improvement activities , which will alleviate the pressure of governments on environmental protection.…”
Section: Discussionmentioning
confidence: 99%
“…There are various control mechanisms to minimize asymmetric information and better control over managerial activities, such as quality and disclosure of social responsibility. Credit rating agencies also tend to evaluate the credit reliability of companies based on their non-financial information, such as sustainability reports (Bao et al, 2020). Therefore, companies with high social responsibility tend to find it easier to get long-term debt (Hung et al, 2020).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…When negative corporate news accumulates for a long time and suddenly breaks out, it will cause negative reactions from investors, leading to the company's stock price turmoil (Kim and Zhang, 2016;Wei and Zeng, 2018;Wu et al, 2019). Therefore, it is important to improve the information environment for stabilizing the financial market (Han et al, 2019;Bao et al, 2020). The more transparent the information disclosed by the company, the lower the stock price crash risk (Hutton et al, 2009).…”
Section: Introductionmentioning
confidence: 99%